Building Corporate Reputation through Corporate Social Re-sponsibility (CSR), Corporate Culture and Value Creation - In The Industry of Sharia Banking in Indonesia - Zaky Maulana, Chandra; Suryana S, Yuyus; Kartini, Dwi; Febrian, Erie (Opción, 2019)
This research aimed to find influence between CSR and corporate culture on the corporate reputation through value crea-tion as the intervening variable in the sha- ria banking industry (Sharia Commercial Banks and Sharia Subsidiary Unit) in Indonesia. This research used explanatory survey method. The approach in the modeling and the technical solution as the tool analysis utilized Structural Equa- tion Modelling (SEM). Data were processed using Lisrel 8.5. The results showed that CSR disclosure and Corporate Culture have direct influence on the reputation of sharia banking in Indonesia 6% and 35% respectively and drew a conclusion in which, CSR disclosure and Corporate Culture influenced the reputation of sharia banking industry in Indonesia and Value Creation was able to mediate the relationship.